Combined control of a distribution static synchronous compensator/flywheel energy storage system for wind energy applications - Suvire, Gaston Orlando (2012)
The integration of wind power generation in power systems is steadily increasing around the world. This incorporation can bring problems onto the dynamics of power systems owing to the lack of controllability over the wind and the type of generation used. In this work, a distribution static synchronous compensator (DSTATCOM) coupled with a flywheel energy storage system (FESS) is used to mitigate problems introduced by wind generation in the electrical systems. A dynamic model of the DSTATCOM/FESS device is briefly presented and a technique to control the active power exchanged between the device and the power system is proposed. The control technique has two control modes. One control mode mitigates the power fluctuations of wind generators, and it is based on fuzzy logic and a special filter. The other control mode contributes to recover the frequency when significant faults arise in the system. Simulation tests on the behaviour of the device are analysed when it works in combination with wind generation in the electrical system. Results show a satisfactory performance of the proposed control techniques along with a high effectiveness to smooth the active power fluctuations of wind generation and to contribute to the recovery of the frequency.